Assessment of the Abuse Potential of the Orexin Receptor Antagonist, Suvorexant, Compared With Zolpidem in a Randomized Crossover Study. Issue 4 (August 2016) - Schoedel, Kerri A.; Sun, Hong; Sellers, Edward M.; Faulknor, Janice; Levy-Cooperman, Naama; Li, Xiaodong; Kennedy, William P.; Cha, Jang-Ho; Lewis, Nicole M.; Liu, Wen; Bondiskey, Phung; McCrea, Jacqueline B.; et al.
Abstract : Abstract: Suvorexant is a dual orexin receptor antagonist approved in the United States and Japan for the treatment of insomnia at a maximum dose of 20 mg. This randomized double-blind crossover study evaluated the abuse potential of suvorexant in 36 healthy recreational polydrug users with a history of sedative and psychedelic drug use. Single doses of suvorexant (40, 80, and 150 mg: 2–7.5 × maximum dose), zolpidem (15 and 30 mg: 1.5–3 × maximum dose), and placebo were administered, with a 10-day washout between treatments. Subjective and objective measures, including visual analog scales (VASs), Addiction Research Center Inventory, and cognitive/psychomotor tests, were evaluated for 24-hour postdose. Suvorexant had significantly greater peak effects on "drug liking" VAS (primary endpoint) than placebo. Although effects of suvorexant on abuse potential measures were generally similar to zolpidem, they remained constant across doses, whereas zolpidem often had greater effects at higher doses. Suvorexant (all doses) had significantly fewer effects than zolpidem 30 mg on secondary measures, such as "high" VAS, Bowdle VAS, and Addiction Research Center Inventory morphine-benzedrine group. The overall incidence of abuse-related adverse events, such as euphoric mood and hallucination, was numerically lower with suvorexant than zolpidem. In agreement with its classification as a schedule IV drug, suvorexant demonstrated abuse potential, compared with placebo. The abuse potential was similar to zolpidem using certain measures, but with a reduced incidence of abuse-related adverse events. Although this suggests that the overall abuse liability of suvorexant may be lower than zolpidem, the actual abuse rates will be assessed with the postmarketing experience. Abstract : Supplemental digital content is available in the text.